2017
DOI: 10.1007/s10561-017-9657-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal predictors and quality of umbilical cord blood units

Abstract: The aim of the study was to determine the relationship between the maternal age at delivery and selected properties of the cord blood stem cells. The study included 50 pregnant women aged between 18 and 38 years in which spontaneous labors or elective cesarean sections were performed. Umbilical cord blood was collected immediately after the women were delivered of newborns. The samples were analyzed in the Polish Stem Cells Bank in Warsaw. The highest mean WBC level (p < 0.05) was observed in the umbilical blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Uji korelasi yang dilakukan untuk melihat 12 Pada kehamilan dengan usia ibu di atas 31 tahun, jumlah sel darah putih lebih banyak dibandingkan usia ibu di bawah 25 tahun. Sel punca darah tali pusat merupakan populasi sel yang berada pada sel darah putih.…”
Section: Hasilunclassified
“…Uji korelasi yang dilakukan untuk melihat 12 Pada kehamilan dengan usia ibu di atas 31 tahun, jumlah sel darah putih lebih banyak dibandingkan usia ibu di bawah 25 tahun. Sel punca darah tali pusat merupakan populasi sel yang berada pada sel darah putih.…”
Section: Hasilunclassified
“…The effect of maternal and neonatal factors on the quality of umbilical cord blood stems cells have been a subject of numerous studies [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. One of the deciding factors in the usefulness of cord blood is the number of CD34+ stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in this study, the correlation between the mode of delivery, the age of the mother and the quality of the obtained material for transplantation was assessed. The older the women from whom umbilical cord blood was collected, the lower the mean concentration of HSC cells in the material [ 37 ]. Aufderhaar et al showed that perinatal factors such as low blood pH and prolonged first stage of labor correlate with increases in CD34+ cells and cord blood progenitor cells [ 45 ].…”
Section: Introductionmentioning
confidence: 99%